2020
DOI: 10.1007/s10826-020-01844-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Anger Expression Mediate the Relationship Between Parental Rejection and Direct and Indirect Forms of Non-suicidal Self-injury?

Abstract: Non-suicidal self-injury (NSSI) is defined as the intentional destruction of one’s own body without an intent to die (e.g., self-cutting). On the other hand, indirect forms of self-injury refer to behaviors in which people harm themselves in an indirect way (e.g., substance use). Existing literature suggests that a negative parent–child relationship may increase vulnerability to NSSI and indirect forms of self-injury. However, little is known about the potential mediators that intervene in the aforementioned r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
(85 reference statements)
2
10
0
Order By: Relevance
“…According to the experiential avoidance model of NSSI ( 22 ), negative emotions usually precede NSSI, and adolescents may engage in NSSI as a means of avoiding these emotions. Our findings are consistent with this model and with other research showing that negative emotions (such as depression, anxiety, and anger expression) are a particularly significant trigger of adolescent NSSI ( 6 , 16 , 30 , 44 , 45 , 53 ). Our results, together with those of earlier research, provide evidence of a mediated pathway in which stressful life events increase the risk of negative emotions, which in turn increases the risk of NSSI.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…According to the experiential avoidance model of NSSI ( 22 ), negative emotions usually precede NSSI, and adolescents may engage in NSSI as a means of avoiding these emotions. Our findings are consistent with this model and with other research showing that negative emotions (such as depression, anxiety, and anger expression) are a particularly significant trigger of adolescent NSSI ( 6 , 16 , 30 , 44 , 45 , 53 ). Our results, together with those of earlier research, provide evidence of a mediated pathway in which stressful life events increase the risk of negative emotions, which in turn increases the risk of NSSI.…”
Section: Discussionsupporting
confidence: 93%
“…The findings supported our hypothesis that adolescents who experienced stressful life events are more likely to engage in NSSI. This result confirmed the findings from previous studies that showed a significant positive correlation between stressful life events and adolescent NSSI ( 16 18 , 44 ). This result also is consistent with what would be expected based on the general strain theory ( 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations